Synthesising knowledge for lean product development process of a low noise jet engine - Araci, Zehra Canan; Al-Ashaab, Ahmed; Tariq, Muhammad Usman; Braach, Jan H. (Inderscience, 2021)
The product development process is one of the most challenging stages of a product life cycle due to several reasons. Having the right knowledge environment during the design process may eliminate the waste of cost and time. The aim of this paper is to demonstrate a case study where designers can investigate the conflicting parameters about a product and make their decisions based on an accurate knowledge environment that is created by trade-off curves. The product in consideration is a turbofan jet engine with a requirement of noise reduction during takeoff while keeping up with high quality standards.
Keywords: decision making; aircraft engine noise reduction; trade-off curves; new product development,; lean product development; knowledge management; knowledge creation and visualisation